Emotional Dysregulation in Adolescents: Implications for the Development of Severe Psychiatric Disorders, Substance Abuse, and Suicidal Ideation and Behaviors - De Berardis, Domenico (Brain Sci, 2020)
Well-tuned emotional regulation is fundamental for human life and psychological well-being. Negative physiological emotions are counterbalanced by positive ones, and this equilibrium is the mainstay of human physiological affective states. However, this mechanism may sometimes become dysfunctional when negative emotions are not correctly counterbalanced, causing maladaptive behaviors, especially during adolescence. A very interesting review by Young et al. was recently published (Brain Sci. 2019, 9(4), 76) and stimulated us to reflect on this topic. The screening for emotional disturbances and dysregulation in adolescents must be included in all the preventive and interventional programs aimed to achieve both physical and psychological well-being of the population and early intervention should be provided in order to avoid progression toward clinically relevant psychiatric disorders in late adolescence and adulthood.